Pengaruh Jenjang Pendidikan, Partisipasi Pemakai Sistem Informasi Akuntansi, Skill, Terhadap Efektivitas Sistem Informasi Akuntansi di LPD Se Kecamatan Denpasar Utara - Ni Wayan Merliana Dewi; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2022)
LPD (Lembaga Perkreditan Desa) is a traditional financial institution with low resources and limited technology. In this era of digitalization, it is important to encourage village financial institutions to use technology in serving the community so that village financial institutions are strong, able to compete, and educated and certified human resources are absolute should-have for LPDs. The purpose of this study was to determine the effect of education level, participation of accounting information system users, and skills on the effectiveness of accounting information systems. This study's population was conducted in 10 LPDs in North Denpasar Sub-District that met the criteria. The purposive sampling method was used to determine the number of samples in this study, which totaled 62 employees. According to the findings of this study, education level, participation of accounting information system users, and skills all have a positive and significant impact on the effectiveness of accounting information systems in the LPD of North Denpasar Sub-District.